Serological evidence and experimental infection of cynomolgus macaques with pteropine orthoreovirus reveal monkeys as potential hosts for transmission to humans - Chee Wah Tan; Kevin Wittwer; Xiao Fang Lim; Anna Uehara; Shailendra Mani; Lin-Fa Wang; Danielle E. Anderson (Emerging Microbes and Infections, 2019)
ABSTRACTPteropine orthoreoviruses (PRV) are emerging bat-borne viruses with proven zoonotic transmission. We recently demonstrated human exposure to PRV in Singapore, which together with previous reports from Malaysia and Vietnam suggest that human infection of PRV may occur periodically in the region. This raises the question whether bats are the only sources of human infection. In this study, we screened 517 cynomolgus macaques caught in Singapore for evidence of exposure to PRV3M (also known as Melaka virus), which was first isolated from human patients in Melaka, Malaysia. We found that 67 serum samples were PRV3M positive by ELISA and 34 were also positive by virus neutralization assay. To investigate whether monkeys could act as hosts for PRV transmission, we experimentally infected cynomolgus macaques with PRV3M and housed these animals with uninfected monkeys. Although no clinical signs of infection were observed in infected animals, viral RNA was detected in nasal and rectal swabs and all infected macaques seroconverted. Additionally, one of the uninfected animals seroconverted, implying active shedding and transmission of PRV3M. We provide evidence that PRV exposure in the macaque population in Singapore occurs at a relatively high prevalence and this study suggests that cynomolgus macaques may be an intermediate or reservoir host for PRVs.